capB2 Expression Is Associated with Staphylococcus aureus Pathogenicity - Li, Dan; Guo, Yinjuan; Wang, Shanshan; Lv, Jingnan; Qi, Xiuqin; Chen, Zengqiang; Han, Lizhong; Zhang, Xueqing; Wang, Liangxing; Yu, Fangyou (Frontiers in Microbiology, 2017)
CapB2 is recognized as a tyrosine kinase and is likely a vital factor in extracellular polysaccharide synthesis in Staphylococcus aureus, but its pathogenicity function and regulatory mechanism remain obscure. Here we demonstrate that CapB2 enhances bacterial virulence in a murine model. Mice infected with the wild-type SA75 strain exhibited significantly larger (P<0.05) skin lesions from days 4-7 of infection than those challenged with the capB2 mutant strain. The effect on virulence was reverted by restoring the capB2 mutation to the wild-type. The related components of the wild-type SA75 cell wall in the capB2 mutant strain (SA75ΔcapB2) were thinner than wild-type SA75 strain and the capB2 mutant complemented strain (SA75ΔcapB2-C), which was determined by the transmission electron microscopy. The survival percentages of the wild type strain SA75 and SA75ΔcapB2-C were significantly higher relative to SA75ΔcapB2. The results of qRT-PCR studies also indicated that mutations in regulatory gene sarA led to a drastic increase in capB2 gene transcription, with a 326-fold increase of growth at 6h compared with the wild type strain, suggesting that sarA is a major negative regulator of capB2 expression. Taken together, these results demonstrate that the expression of CapB2 promotes S. aureus virulence in a mouse model of skin infection, and that capB2 gene transcription is regulated negatively by SarA.